Hierarchy in zeolite catalysis: The influence of enhanced mesoporosity on the synthesis of renewable fuels and bio-based platform chemicals - Al-Ani, Aqeel; Freitas, Catia; Zholobenko, Vladimir (Journal of Petroleum Research and Studies, 2020)
Faujasite (FAU), ZSM-5 (MFI), beta (BEA) and mordenite (MOR) zeolites were admitted to a variety of chemical treatments accompanied by surfactant templating strategy, aiming to introduce the intracrystalline mesoporosity effectively. The resulting materials were tested as solid acid catalysts for esterification of the oleic acid as a common model impurities found in bio-oil feedstoks. It was found that the esterification of oleic acid can be enhanced by the presence of strong acid sites in zeolites and their improved accessibility. Overall, mesostructured FAU zeolite demonstrated an improved catalytic performance as a result of increasing accessibility of the zeolite active sites.